2007
DOI: 10.1002/jgm.1058
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and internalization following vector adsorption to immobilized proteins: dependence on protein identity and density

Abstract: Background-Gene delivery by non-specific adsorption of non-viral vectors to protein-coated surfaces can reduce the amount of DNA required, and also increase transgene expression and the number of cells expressing the transgene. The protein on the surface mediates cell adhesion and vector immobilization, and functions to colocalize the two to enhance gene delivery. This report investigates the mechanism and specificity by which the protein coating enhances gene transfer, and determines if the protein coating ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
90
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 51 publications
2
90
0
Order By: Relevance
“…In addition, when analyzing the influence of FBS protein coatings on substrate immobilization of DNA-NPs, the SE/QCM-D data suggest that DNA-NP immobilization efficiency is substrate dependent, since different DNA-NP immobilization trends are observed between different substrates coated with FBS ( Table 2). The two previous observations, together, suggest that although similar amounts of protein are adsorbing to the substrate with similar packing characteristics, different proteins within the FBS mixture, including different protein functional groups and binding motifs for DNA-NPs, could be presented on different substrates, as indicated by differences in detected DNA-NP quantities and porosities between the three substrates, as well as reported differences in transfection efficiencies [9,11,32]. Previous work regarding fibronectin protein adsorption to different SAM surfaces has shown that different surface characteristics, such as charge and hydrophobicity, influences the conformation of adsorbing proteins [33], which could influence subsequent adsorption of biomolecules, such as DNA-NPs, due to the exposure of different protein functional groups between surfaces.…”
Section: Substrates Influence Dynamic Immobilization Properties Of Dnmentioning
confidence: 89%
See 4 more Smart Citations
“…In addition, when analyzing the influence of FBS protein coatings on substrate immobilization of DNA-NPs, the SE/QCM-D data suggest that DNA-NP immobilization efficiency is substrate dependent, since different DNA-NP immobilization trends are observed between different substrates coated with FBS ( Table 2). The two previous observations, together, suggest that although similar amounts of protein are adsorbing to the substrate with similar packing characteristics, different proteins within the FBS mixture, including different protein functional groups and binding motifs for DNA-NPs, could be presented on different substrates, as indicated by differences in detected DNA-NP quantities and porosities between the three substrates, as well as reported differences in transfection efficiencies [9,11,32]. Previous work regarding fibronectin protein adsorption to different SAM surfaces has shown that different surface characteristics, such as charge and hydrophobicity, influences the conformation of adsorbing proteins [33], which could influence subsequent adsorption of biomolecules, such as DNA-NPs, due to the exposure of different protein functional groups between surfaces.…”
Section: Substrates Influence Dynamic Immobilization Properties Of Dnmentioning
confidence: 89%
“…For example, Bengali et al [9], reported that increasing concentrations of DNA-PEI NPs added to FBS-coated polystyrene surfaces did not influence the adsorbed mass of DNA, an observation that contradicts the trend from the SE/QCM-D results shown in Figure 1. However, SE/QCM-D provides a more precise perspective of DNA-NPs associated with a surface, since loosely bound, passively adsorbed DNA-NPs are also evaluated with SE/QCM-D. For previously reported radioactivity measurements, loosely bound DNANPs would have been washed off the surface during rinse steps before even conducting admeasurement, thus measuring only tightly bound DNA-NPs, which explains why QCM-D detects an increased mass of adsorbed and loosely associated DNA-NPs relative to previous studies [7][8][9]11]. Another important difference to note is that previous DNA radiolabeling studies reported the adsorbed mass of DNA instead of the entire DNA-NP complex since DNA was the labeled component that was measured.…”
Section: Dna-np Concentration Influences Dna Immobilization Efficiencymentioning
confidence: 99%
See 3 more Smart Citations